АКАДЕМИК ЛИЦЕЙЛАРДА МАТЕМАТИКА ФАНИНИ ЙЎНАЛИШЛАРГА БОҒЛАБ ЎҚИТИШ МЕТОДИКАСИ - Джакаева, К.Д. (SCIENCE and SOCIETY, 2018)
The article deals with the issues of methods of teaching Mathematics as an applied science, at the academic lyceums and also about syllabus in natural sciences, philology and foreign languages, and social-humanitarian disciplines.
Keywords: specialization direction; professional experience; professional skills; interest in science; independent thinking